The Negative Relationship between Intrnet Access and Economic Growth: Evidence from the Indonesian - Suparta, I Wayan; Erda, Melinda Dwi; Wahyudi, Heru (Journal of Ecohumanism, 2024)
The internet is closely linked to economic growth, including increased productivity, innovation and entrepreneurship, access to global markets, skills development and education, digital infrastructure and services, and increased connectivity and collaboration. The internet is growing rapidly in Indonesia, especially on the island of Java. Java as the largest economic contributor in Indonesia, followed by Sumatra Island as the second contributor. For this reason, this study aims to examine the influence of internet access, the number of mobile phone users, the number of BTS towers, and the Labor force participation rate on economic growth in Java and Sumatra for the 2018-2021 period partially and simultaneously. The analysis methods used are model suitability testing, classical assumption testing, panel data linear regression model, hypothesis test with t-test and f-test and determination coefficient interpretation. The results of the study show that internet access as a proxy for access to technological progress, has a negative effect on economic growth. Internet access, the number of mobile phone users, the number of BTS towers, and Labor force participation rate together have a significant effect on economic growth in Java and Sumatra Indonesia for the 2018-2021 period.